A supply-demand matching and trading service platform for energy-saving and emission-reduction technology. (2016) - Wang, Yuqi; Zuo, Ying
In order to solve the current problem of information asymmetry for both sides of supplier and demander on energy-saving and emission-reduction (ESER) technology, the business requirements of ESER technology platform was analysed first in this paper. Then a four-layered architecture ESER technology service trading platform, which combined with the characteristics of the existing electronic service trading platform, was proposed. According to this architecture, the function modules of the platform and the data physical structure model of database which supports the platform's running was designed in this paper. Finally, a prototype system was developed and the corresponding trading operation process was given, which verified the feasibility and effectiveness of the proposed approach.